Mjölnir, from Brand Management's Point of View: The strength of the brand in Iceland - Kospenda, Nemanja, 1994- (2017)
Combat sports in Iceland have gained increased popularity in recent years. Competition has increased among organizations as they strive to gain competitive advantage and simultaneously strengthening their brand. Most organizations rely on marketing to advertise their brand and it is mostly conducted through social media such as Facebook and Twitter. It is important for an organization to affect what comes into the minds of their consumers when they associate with their brand. The purpose of this thesis is to analyze the strength of the brand Mjölnir. The main objective of this thesis is to explore the strength of Mjölnir compared to other mixed martial arts brands in Iceland, as well as analyze what makes a brand strong and the theoretical methods behind it. The thesis begins with defining what a brand is and presents the aspects of brand management. A comparison is done between the theoretical methods of brand management with the deployed methods of Mjölnir. The thesis is set up in a form of a theoretical discussion of the main aspects of brand management and a qualitative research. At the end of the theoretical discussion, the strength of the brand in Iceland was evaluated. The key findings of this thesis are that there are many benefits of having a strong brand such as increased consumer loyalty and brand equity. In the case of Mjölnir, having a strong brand has resulted in increased amounts of participants, compared to rival organizations, and increased brand loyalty among their consumers.